Efektivitas Pelaksanaan Silayda E-KTP - Ary Ananda Pane; Adi Syahputra Sirait (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
The Effectiveness of the Implementation of SILAYDA (Online Service System) at the Department of Population and Civil Registry of Padangsidimpuan City which is reviewed in the Regulation of the Minister of Home Affairs of the Republic of Indonesia No. 7 of 2019 concerning Online Population Administration Services. The problem that occurs is to find out whether the implementation of the SILAYDA (Online Service System) at the Padangsidimpuan City Population and Civil Registry Service makes it easier for the community to manage ID cards or vice versa at the Padangsidimpuan City Population and Civil Registry Office. The formulation of the problem of this research is the problems that occur are to find out how the effectiveness of the implementation of SILAYDA (Online Service System) EKTP at the Population and Civil Registration Office of Padangsidimpuan City and to find out what are the obstacles in the implementation of the implementation of SILAYDA (Online Service System) E -KTP at the Population and Civil Registry Office of Padangsidimpuan City. The type of research that the author uses is field research which takes place at the Department of Population and Civil Registry of Padangsidimpuan City. Meanwhile, to manage and analyze the data is done by identification, category, analysis, and conclusion. The results obtained from this study indicate that in the Implementation of the SILAYDA (Online Service System) EKTP at the Population and Civil Registry Office of Padangsidimpuan City which is reviewed in the Regulation of the Minister of Home Affairs of the Republic of Indonesia No. 7 of 2019 concerning Online Population Administration Services, greatly facilitates the people of Padangsidimpuan City in managing ID cards at the Padangsidimpuan City Population and Civil Registry Office